SPA vulnerabilities of the binary extended Euclidean algorithm - Aldaya, Alejandro Cabrera; Sarmiento, Alejandro J. Cabrera; Sánchez-Solano, Santiago (Journal of cryptographic engineering, 2017)
The execution flow of the binary extended Euclidean algorithm (BEEA) is heavily dependent on its inputs. Taking advantage of that fact, this work presents a novel simple power analysis (SPA) of this algorithm that reveals some exploitable power consumption-related leakages. The exposed leakages make it possible to retrieve some bits of the algorithm’s secret input without profiling the target device. The identified vulnerabilities can be exploited in many cryptographic protocols where the modular inversion operation is applied to a secret argument. In this work, the ECDSA protocol is used to exemplify how the presented SPA can be used to disclose in about 2 min all standardized private key sizes using less than 800 traces. In the context of ECDSA, a countermeasure previously proposed to mitigate a timing leakage during scalar multiplication is also analyzed, showing that, when it is improperly implemented, it enhances the proposed bit recovery method. Three countermeasures for removing SPA leakages from a BEEA implementation are also analyzed.